Fuel analyses and rank determination of the Egyptian Maghara main coal seam, north central Sinai, Egypt - N.A.A. Edress; A.R. Abdel-Fatah (Egyptian Journal of Petroleum)
Three geologic sections along the main coal seam (MCS) of the Middle Jurassic (Bathonian) Safa Formation of Maghara mine are examined. Samples collected have been studied. The fuel analyses of coal samples were conducted to determine their Rank characteristic. Fuel analysis classified the studied Maghara MCS as high grade coal, medium rank (D) of para-bituminous class based on its average values of ash content 7.1% (dry-base; d.b), gross calorific value (29 Mj/kg; moist ash free) and random vitrinite reflectance 0.43%. Synonym nomenclature of the studied Maghara coal based to ASTM classification is high volatile (C) class of bituminous group with agglomerating character attributed to their values of gross calorific value 30 Mj/kg-(moist-mineral-matter-free; mmmf), fixed carbon 45% (dry-mineral-matter-free; dmmf) and volatile matter 54.8% dmmf. Elemental ratio of H/C versus O/C indicate that majority of the studied Maghara coal samples occupy the area of vitrinite genesis pathway on Van-Krevelen diagram, and within the area of per-hydrous in Seyler chart of dominated anoxic condition. Studied coal seam is a type III kerogen corresponding to humic characteristic, within the immature and mature zones of coalification. Keywords: Coal, Maghara coal, Sinai, Egypt, Fuel analyses, Rank determination